Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.5194/egusphere-egu21-6760
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Two classes of eruptive events during Solar Minimum

Abstract: <p>During Solar Minimum, the Sun is perceived to be quite inactive with barely any spots emerging on the solar surface. Consequently, we observe a drop in the number of highly energetic events such as solar flares and coronal mass ejections (CMEs), which are often associated with active regions on the photosphere. However, our magnetofrictional simulations during the minimum period suggest that the solar corona could still be significantly dynamic while evolving in response to the large-scale she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…This idea was introduced by van Ballegooijen et al (2000), who modelled the evolution of the large-scale coronal magnetic field in response to both large-scale solar surface motions (primarily differential rotation) and small-scale (supergranular) convection, which they parametrised by a surface diffusion term. They showed that this simple model can capture the formation of sheared filament channels, and even the sudden eruption of twisted magnetic structures due to loss of equilibrium (e.g., Mackay and Yeates 2012, Lowder and Yeates 2017, Bhowmik and Yeates 2021. The MF model has also been applied with resolved smallscale boundary driving, using either an imposed convective velocity field (Meyer and Mackay 2016) or an imposed electric field constrained by observed magnetograms (Mackay et al 2011, Cheung and DeRosa 2012, Pomoell et al 2019, Hoeksema et al 2020, Yardley et al 2021.…”
Section: Introductionmentioning
confidence: 99%
“…This idea was introduced by van Ballegooijen et al (2000), who modelled the evolution of the large-scale coronal magnetic field in response to both large-scale solar surface motions (primarily differential rotation) and small-scale (supergranular) convection, which they parametrised by a surface diffusion term. They showed that this simple model can capture the formation of sheared filament channels, and even the sudden eruption of twisted magnetic structures due to loss of equilibrium (e.g., Mackay and Yeates 2012, Lowder and Yeates 2017, Bhowmik and Yeates 2021. The MF model has also been applied with resolved smallscale boundary driving, using either an imposed convective velocity field (Meyer and Mackay 2016) or an imposed electric field constrained by observed magnetograms (Mackay et al 2011, Cheung and DeRosa 2012, Pomoell et al 2019, Hoeksema et al 2020, Yardley et al 2021.…”
Section: Introductionmentioning
confidence: 99%